Hubungan Beban Kerja Dengan Kelengkapan PencatatanHasil Pengukuran Pada Formulir PembuatanOrtosis Prostesis Di Cv. Kuspito - PRATOMO , RIWI ARIF (2012)
Prosthetis Orthotis responsible for recording the results of measurements on a form making prosthesis orthosis, the measurement process is a very important process in the manufacture of which must be carefully and thoroughly during the following measurements can later be used according to the size of the patient's limb. The purpose of this study to correlate with the work load on the completeness of recording of measurement results in the form of making a prosthesis orthosis CV. Kuspito. This is an observational analitic research with approach time series. Object of study in this research is the form of making prosthesis orthosis that has been filled by officers when there are new patients.The process of analysis using rank spearman ( r ).The results showed that there was no correlation between officer's workload with the completeness measurement result in form making prosthesis orthosis, with the results of analysis, the value of p = 0.195 (p> 0.05) r =-0,243.